PENCATATAN PERKAWINAN SEBAGAI PERLINDUNGAN HUKUM DALAM PERSPEKTIF MAQĀṢID ASY-SYARĪ’AH - Zubaidah, Dwi Arini (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
Procedural rules for marriage recording have led to speculation that marriage records are only considered more administrative requirements. So that up to now under-age marriages are still often found among the public. The purpose of this study is to show the urgency of a marriage record for those bound by marriage. The type of research used is library research and descriptive analysis that describes objectively the rules of marriage recording by analyzing using the theory of maqāṣid ash-syarī'ah as a methodology approach to the philosophy of Islamic law. Based on the results of the study, the rules for recording marriage are a product of Islamic law reform that is at the forefront of the present. Marriage registration is a renewal of Islamic law as a new form of ijtihad towards witnessing in a marriage. By registering the marriage civil rights of the parties concerned will be guaranteed and secure. A marriage that is carried out may not be enough with a testimony according to existing marriage conditions. The logical consequence of the development of the developing period is also evidence that determines the validity of marriage. Features of Jāsir system theory udah Audah is six, namely the character of cognition, overallness, openness, interrelated hierarchy, multidimensionality, and intentions. The whole feature of Jāsir udah Audah is applicative which can realize the idea of the rules of marriage registration as a legitimate condition for determining a marriage.